Demography and Labor Markets - Ilya Pavlov (Journal of Economic Sociology, 2017)
The XVIIIth April International Academic Conference on Economic and Social Development, which was organized at the Higher School of Economics, included a section on “Demography and Labor Markets”. The first day was devoted to the problems of registration and methods of analysis of population data, migrants in contemporary Russia and their integration into the Russian economy, and the use of data mining tools in demographic research. On the second day, there was a discussion of workers’ subjective well-being, unemployment, and global and regional labor markets. The list of speakers included B. Rao and P. Singh (both: Indian Institute of Technology Roorkee), A. Sulaberidze (Ilia State University, Georgia), S. Biryukova, D. Gizdatullin, D. Ignatov, E. Mitrofanova, A. Muratova, E. Papanova, E. Polyakova, A. Rezyapova, A. Shevchuk, E. Soroko, D. Strebkov, E. Vardanyan, and N. Voronina (National Research University Higher School of Economics), Y. Florinskaya and I. Kazenin (Russian Presidential Academy of National Economy and Public Administration under the President of the Russian Federation), Т. Blinova, K. Doronina, P. Sushko (Russian Academy of Sciences), and M. Giltman (Tyumen State University). Russian experts in labor economics, demography, and math, namely S. Roshchin, A. Vishnevsky, L. Smirnykh, V. Gimpelson, M. Denisenko, R. Kapelyushnikov, A. Makarov, and N. Mkrtchyan, also took part in the discussion.